The Teaching Of Religious Moderation In The Arba’in Hadith Of Mahfuzh al-Tarmasi and The Arba'in Hadith Of Hasyim Ash'ari - Muhammad Rikza Muqtada (Jurnal Ushuluddin, 2019)
In the first of 20th century, there were two local hadith books written by two archipelago scholars whose teacher and student status, namely the al-Minhah al-Khairiyah fî Arba’îna Hadîtsan min Ahâdîtsi Khair al-Bariyyah by Mahfuzh al-Tarmasi (d. 1919/1920 AD) and the Arba’ûna Hadîtsan Tata’allaqu bi Mabâdi’u Jam’iyyatu Nahdlatu al-Ulamâ’ by Hasyim Ash'ari (d. 1947 AD). Both of books have a different theme structure from the Arba'in tradition books written by their teachers in the Middle East. For this reason, this paper focuses on how the writing context and the intelectual discourse are contained in the text. The two books of Arba’in hadith were written in order to counter wahabism that at that time attacked the religious thoughts and practices of the archipelago Muslims with the accusations of takfirism. The morality in these books is more directed to moderate the attitudes towards anyone, even against the enemy. As like Ritchey, yellow book or turats is an effective medium for moderating religious attitudes in Islam